Land use influences dissolved organic matter composition in the U.S. Coastal Critical Zone Network - Aleksandar I. Goranov; Elizabeth V. Whitney; Brian R. Moyer; Katherine L. Tully; Patrick G. Hatcher; Yu-Ping Chin (Aquatic Sciences, 2026)
Coastal watersheds are highly productive biogeochemical systems supporting robust coastal fisheries and contributing significantly to the marine gross primary production flux. These ecosystems are comprised of civil infrastructure, farms, forests, and marshes, and their diversity is reflected in the quantity and quality of dissolved organic matter (DOM). Here, we assess the role of farming in influencing DOM from surface waters of six coastal tidal creeks adjacent to forest and farm sites in the US Critical Zone Network. Molecular fingerprinting using electrospray ionization - Fourier transform - ion cyclotron resonance - mass spectrometry revealed that farm-influenced DOM was enriched in nitrogen-, sulfur-, and phosphorus-containing compounds. The concentration of ammonium [NH 4 + ] correlated significantly with nitrogen-containing formulas that could comprise NH 3 adducts, suggesting that NH 4 + (e.g., from fertilizer) can be incorporated into DOM through two-electron chemical reaction pathways such as the Michael addition, one-electron reactions such as Fenton oxidation, or biotic pathways. This suggests the use of [NH 4 + ] measurements as a potential approach to parameterize the impact of agriculture on coastal environments. Collectively, these results establish a foundation for future studies in the U.S. Critical Zone Network on how land and water interact. More broadly, our molecular fingerprinting of DOM corroborated with the global observations of elevated concentrations of nitrogen, sulfur, and phosphorus in farm-influenced freshwater DOM, showing that agricultural activities (e.g., annual fertilizer application) can also influence the DOM composition in coastal environments of high salinity and pH.

Variations in lignin content deposited in the Congo fan and its potential for oxidative degradation - Louis C. Bondurant; Megan L. Baker; Sophie Hage; Peter J. Talling; Patrick G. Hatcher (Marine Chemistry, 2025)

Seasonal and longitudinal dynamics of DOM within headwater streams of a tropical evergreen forest - Samantha N. Sullivan; Jennifer C. Bowen; Louis A. Kaplan; Rose M. Cory; Patrick G. Hatcher (Water Research, 2025)

Strong depth-dependent chemical and structural characteristics of dissolved organic matter (DOM) in organic-rich sediment in a shallow temperate lake - Chenhui Wei; Shu Tao; Patrick G. Hatcher; Dongqiang Zhu (Geochimica et Cosmochimica Acta, 2025)

Contrasting molecular structures and photooxidation behaviors between dissolved organic sulfur released from rice straw-biochar and aerobically decomposed rice straw - Chenhui Wei; Heyun Fu; Xiaolei Qu; Shu Tao; Patrick G. Hatcher; Dongqiang Zhu (Chemical Geology, 2025)

Toxicity of crude oil-derived polar unresolved complex mixtures to Pacific herring embryos: Insights beyond polycyclic aromatic hydrocarbons - Maxwell L. Harsha; Yanila Salas-Ortiz; Alysha D. Cypher; Ed Osborn; Eduardo Turcios Valle; Jacob L. Gregg; Paul K. Hershberger; Yuri Kurerov; Sarah King; Aleksandar I. Goranov; Patrick G. Hatcher; Anastasia Konefal; et al. (Science of The Total Environment, 2024)

The impact of biochar's physicochemical properties on sorption of perfluorooctanoic acid (PFOA) - Karen Ane Skjennum; Katinka M. Krahn; Erlend Sørmo; Raoul Wolf; Aleksandar I. Goranov; Patrick G. Hatcher; Thomas Hartnik; Hans Peter H. Arp; Andrew R. Zimmerman; Yaxin Zhang; Gerard Cornelissen (Science of The Total Environment, 2024)

Interaction between peptide and solid lignin suggest mechanisms of abiotic covalent bond formation - João Vitor dos Santos; Amanda Koenig; Patrick G. Hatcher (Organic Geochemistry, 2024)

Molecular features of uranium-binding natural organic matter in a riparian wetland determined by ultrahigh resolution mass spectrometry - Chen Xu; Aleksandar I. Goranov; Daniel I. Kaplan; Peng Lin; Chris M. Yeager; Nicole Patterson; Helen Jiang; Patrick G. Hatcher; Peter H. Santschi (Science of The Total Environment, 2024)

Biogeochemistry of dissolved organic matter and inorganic solutes in soil profiles of tropical pasturelands - João Vitor dos Santos; Aleksandar I. Goranov; Lucas R. Bento; Patricia P.A. Oliveira; José R.M. Pezzopane; Alberto C.C. Bernardi; Ívero P. de Sá; Ana Rita A. Nogueira; Ladislau Martin-Neto; Patrick G. Hatcher (Soil and Tillage Research, 2024)

Using the benzenepolycarboxylic acid (BPCA) method to assess activated biochars and their PFAS sorption abilities - Aleksandar I. Goranov; Erlend Sørmo; Nikolas Hagemann; Gerard Cornelissen; Andrew R. Zimmerman; Patrick G. Hatcher (Chemosphere, 2024)

Two-step hydrothermal liquefaction of Scenedesmus/Desmodesmus algae for the production of hydrocarbon-based fuels - Louis C. Bondurant; Wassim Obeid; Patrick G. Hatcher (Organic Geochemistry, 2023)

The role of oxygen in stimulating methane production in wetlands - Jared L. Wilmoth; Jeffra K. Schaefer; Danielle R. Schlesinger; Spencer W. Roth; Patrick G. Hatcher; Julie K. Shoemaker; Xinning Zhang (Global Change Biology, 2021)
Methane (CH 4 ), a potent greenhouse gas, is the second most important greenhouse gas contributor to climate change after carbon dioxide (CO 2 ). The biological emissions of CH 4 from wetlands are a major uncertainty in CH 4 budgets. Microbial methanogenesis by Archaea is an anaerobic process accounting for most biological CH 4 production in nature, yet recent observations indicate that large emissions can originate from oxygenated or frequently oxygenated wetland soil layers. To determine how oxygen (O 2 ) can stimulate CH 4 emissions, we used incubations of Sphagnum peat to demonstrate that the temporary exposure of peat to O 2 can increase CH 4 yields up to 2000‐fold during subsequent anoxic conditions relative to peat without O 2 exposure. Geochemical (including ion cyclotron resonance mass spectrometry, X‐ray absorbance spectroscopy) and microbiome (16S rDNA amplicons, metagenomics) analyses of peat showed that higher CH 4 yields of redox‐oscillated peat were due to functional shifts in the peat microbiome arising during redox oscillation that enhanced peat carbon (C) degradation. Novosphingobium species with O 2 ‐dependent aromatic oxygenase genes increased greatly in relative abundance during the oxygenation period in redox‐oscillated peat compared to anoxic controls. Acidobacteria species were particularly important for anaerobic processing of peat C, including in the production of methanogenic substrates H 2 and CO 2 . Higher CO 2 production during the anoxic phase of redox‐oscillated peat stimulated hydrogenotrophic CH 4 production by Methanobacterium species. The persistence of reduced iron (Fe(II)) during prolonged oxygenation in redox‐oscillated peat may further enhance C degradation through abiotic mechanisms (e.g., Fenton reactions). The results indicate that specific functional shifts in the peat microbiome underlie O 2 enhancement of CH 4 production in acidic, Sphagnum ‐rich wetland soils. They also imply that understanding microbial dynamics spanning temporal and spatial redox transitions in peatlands is critical for constraining CH 4 budgets; predicting feedbacks between climate change, hydrologic variability, and wetland CH 4 emissions; and guiding wetland C management strategies.

Aggregation and Degradation of Dispersants and Oil by Microbial Exopolymers (ADDOMEx): Toward a Synthesis of Processes and Pathways of Marine Oil Snow Formation in Determining the Fate of Hydrocarbons - Antonietta Quigg; Peter H. Santschi; Chen Xu; Kai Ziervogel; Manoj Kamalanathan; Wei-Chun Chin; Adrian B. Burd; Andrew Wozniak; Patrick G. Hatcher (Frontiers in Marine Science, 2021)
Microbes (bacteria, phytoplankton) in the ocean are responsible for the copious production of exopolymeric substances (EPS) that include transparent exopolymeric particles. These materials act as a matrix to form marine snow. After the Deepwater Horizon oil spill, marine oil snow (MOS) formed in massive quantities and influenced the fate and transport of oil in the ocean. The processes and pathways of MOS formation require further elucidation to be better understood, in particular we need to better understand how dispersants affect aggregation and degradation of oil. Toward that end, recent work has characterized EPS as a function of microbial community and environmental conditions. We present a conceptual model that incorporates recent findings in our understanding of the driving forces of MOS sedimentation and flocculent accumulation (MOSSFA) including factors that influence the scavenging of oil into MOS and the routes that promote decomposition of the oil post MOS formation. In particular, the model incorporates advances in our understanding of processes that control interactions between oil, dispersant, and EPS in producing either MOS that can sink or dispersed gels promoting microbial degradation of oil compounds. A critical element is the role of protein to carbohydrate ratios (P/C ratios) of EPS in the aggregation process of colloid and particle formation. The P/C ratio of EPS provides a chemical basis for the “stickiness” factor that is used in analytical or numerical simulations of the aggregation process. This factor also provides a relative measure for the strength of attachment of EPS to particle surfaces. Results from recent laboratory experiments demonstrate (i) the rapid formation of microbial assemblages, including their EPS, on oil droplets that is enhanced in the presence of Corexit-dispersed oil, and (ii) the subsequent rapid oil oxidation and microbial degradation in water. These findings, combined with the conceptual model, further improve our understanding of the fate of the sinking MOS (e.g., subsequent sedimentation and preservation/degradation) and expand our ability to predict the behavior and transport of spilled oil in the ocean, and the potential effects of Corexit application, specifically with respect to MOS processes (i.e., formation, fate, and half-lives) and Marine Oil Snow Sedimentation and Flocculent Accumulation.

Comparison of hydrophobic and amphiphilic fractions of dissolved organic matter from a water reservoir by Fourier transform ion cyclotron resonance mass spectrometry - Guixue Song; Rajaa Mesfioui; Aaron Dotson; Paul Westerhoff; Patrick Hatcher (Journal of Soils and Sediments, 2018)

Developing an understanding of dissolved organic matter dynamics in the giant Lake Baikal by ultrahigh resolution mass spectrometry - Yuko Sugiyama; Patrick G. Hatcher; Rachel L. Sleighter; Tomoyo Suzuki; Chizuru Wada; Tetsu Kumagai; Osamu Mitamura; Toshiya Katano; Shin-ichi Nakano; Yuji Tanaka; Valentin V. Drucker; Vladimir A. Fialkov; et al. (Limnology, 2014)

Illuminated darkness: Molecular signatures of Congo River dissolved organic matter and its photochemical alteration as revealed by ultrahigh precision mass spectrometry - Aron Stubbins; Robert G. M. Spencer; Hongmei Chen; Patrick G. Hatcher; Kenneth Mopper; Peter J. Hernes; Vincent L. Mwamba; Arthur M. Mangangu; Jose N. Wabakanghanzi; Johan Six (Limnology and Oceanography, 2010)
Congo River water was filtered and then irradiated for 57 d in a solar simulator, resulting in extensive photodegradation of dissolved organic matter (DOM). Whole‐water (i.e., unfractionated) DOM was analyzed pre‐ and post‐irradiation using ultrahigh resolution Fourier transform ion cyclotron mass spectrometry (FT‐ICR MS), revealing the following three pools of DOM classified based upon their photoreactivity: (1) photo‐resistant, (2) photo‐labile, and (3) photo‐produced. Photo‐resistant DOM was heterogeneous, with most molecular classes represented, although only a small number of aromatics and no condensed aromatics were identified. The photoproduced pool was dominated by aliphatic compounds, although it included a small number of aromatics, including condensed aromatics. Aromatic compounds were the most photoreactive, with > 90% being lost upon irradiation. Photochemistry also resulted in a significant drop in the number of molecules identified and a decrease in their structural diversity. The FT‐ICR MS signatures of two classes of refractory organic matter, black carbon and carboxylic‐rich alicyclic molecules (CRAM), were present in the sample prior to irradiation, indicating that the Congo River could be a significant exporter of recalcitrant DOM to the ocean. All black carbon‐like molecules identified in the initial sample were lost during irradiation. Molecular signatures consistent with CRAM were also highly photo‐labile, demonstrating that environmental solar irradiation levels are capable of removing these refractory compounds from aquatic systems. Irradiation also shifted the molecular signature of terrestrial DOM toward that of marine DOM, thereby complicating the task of tracking terrestrial DOM in the ocean.

Characterizing the properties of dissolved organic matter isolated by XAD and C-18 solid phase extraction and ultrafiltration - Sara B. Schwede-Thomas; Yu-Ping Chin; Karl J. Dria; Patrick Hatcher; Edith Kaiser; Barbara Sulzberger (Aquatic Sciences, 2005)